First records of Arcyria marginoundulata Nann.-Bremek. & Y. Yamam. (Myxomycetes) in Poland - Anna Ronikier; Piotr Perz; Piotr Chachuła (Acta Mycologica, 2013)
A new to Poland species of a myxomycete, Arcyria marginoundulata, was found at two distant localities in the southern part of the country. Polish specimens are typical and have all important features characteristic of the species: minute, grey, stipitate sporocarps, calyculus concentrically plicate at margin, spiny capillitium and small spores covered with few irregularly distributed larger warts. The species was found growing on alder female catkins. It seems that this substrate is specific for A. marginoundulata in Europe.